Relationship between percentage of mean arterial pressure at the ankle and mortality in participants with normal ankle-brachial index: an observational study. Issue 3 (25th March 2016) - Li, Yu-Hsuan; Lin, Shih-Yi; Sheu, Wayne Huey-Herng; Lee, I-Te
Abstract : Objectives: Peripheral arterial disease (PAD) is associated with all-cause mortality. Ankle-brachial index (ABI) is the most widely used tool for detecting PAD, but can yield false-negative results in patients with non-compressible vessels. Pulse volume recording may be an alternative tool for assessing PAD in such patients. However, the association between pulse volume recording and all-cause mortality has seldom been reported. We hypothesised that the percentage of mean arterial pressure (%MAP) and upstroke time (UT), which are indexes of the arterial wave obtained on pulse volume recording, can predict mortality. Design: We conducted this as a retrospective cohort study. Setting: Data were collected from the Taichung Veterans General Hospital. Participants: We included 314 participants with complete data on ABI and pulse volume recording performed between June 2007 and November 2011. Primary outcome measure: Mortality data served as the follow-up outcome. Mortality data were obtained from the Collaboration Center of Health Information Application, Ministry of Health and Welfare, Executive Yuan, Taiwan. Results: Participants with ABI ≤0.9 showed a highest mortality rate (p<0.001 in the log-rank test), but the mortality rate was not significantly different between participants with 0.9<ABI≤1.1 and those with 1.1<ABI≤1.3 (p=0.553). Among the participants with 0.9<ABI≤1.3, the high %MAP (>45%) group showed a higher risk of all-cause mortality than the low %MAP (≤45%) group (HR=5.389, p=0.004) after adjustment for ABI, pulse wave velocity, UT, age, sex, blood pressure, serum cholesterol, and history of cardiovascular disease and diabetes. Conclusions: We thus demonstrated that a high %MAP based on pulse volume recording in participants with 0.9<ABI≤1.3 could predict all-cause mortality during 20.3 months of follow-up.